A new upper Pleistocene tapir from Argentina: remarks on the phylogenetics and diversification of neotropical Tapiridae - Ferrero, Brenda Soledad (2007)
A complete skull of a fossil tapir (Perissodactyla: Tapiridae) was recovered from outcrops of the Arroyo Feliciano Formation (Late Pleistocene; Lujanian Age) in the Argentine Mesopotamia and is here recognized as a new species. The phylogenetic relationships of this new taxon, Tapirus mesopotamicus sp. nov., are revealed by cladistic character analysis using several extinct and extant taxa. The taxa included in the analysis are the extinct genera Miotapirus, Paratapirus, and Plesiotapirus, five North American paleospecies Tapirus veroensis, T. haysii, T. johnsoni, T. webbi, and T. polkensis, and all the living species of the genus Tapirus (T. terrestris, T. pinchaque, T. bairdii, and T. indicus). Tapirus mesopotamicus sp. nov is diagnosed by having a robust and long skull with short rostrum relative to total length of cranium, a single and not arched sagittal crest, broad table of frontals on the anterior skull roof, temporal crests converging very near the frontal-parietal suture, palate very arched, premaxilla deeply notched above canine, maxilla and base of zygomatic process strikingly robust, P1 short and quadrangular, and mandibular condyle slender with posterior wall flat or somewhat concave. The resulting cladogram depicts a well-supported clade comprising the South American tapirs. The new taxon T. mesopotamicus sp. nov. groups with its sister taxon T. pinchaque, and together with T. terrestris, form a sister clade to T. bairdii and three North American fossil tapirs.